Tính lồi-lõm của hàm sản xuất một mức với độ co giãn thay thế không đổi - Tú, Tô Cẩm (Journal of Computer Science and Cybernetics, 2016)
On the base of the theorem [4]: Necessary and sufficient conditions for the constancy of elasticity of substitution (sij=s) of one – level production functions y=f(x1, x2,…, xn) is djj +1/(sijxj) = dji, where dji the following theorem is followed: In the region W =xj ³ 0, j=1..n the one-level production functions with constant elasticity of substitution s is: a. Convex in W1 ÌW if and only if b. Concave in W1 if and only if in this region to say the least of it and , where 1,2,..,k if 1,2,..,n and k=1..n.